PENATALAKSANAAN FISIOTERAPI DENGAN MODALITAS TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS), MICRO WAVE DIATHERMY (MWD) DAN WILLIAM FLEXION EXERCISE PADA KASUS LOW BACK PAIN e.c SPONDYLOLISTHESIS - Agus Nurul Hidayah; Sulistianingsih (Rena Cipta Mandiri, 2025)
Low back pain (LBP) due to spondylolisthesis causes pain, muscle spasms, and limited mobility, thereby requiring appropriate physiotherapy management. The aim of this study was to evaluate the effectiveness of physiotherapy interventions using Transcutaneous Electrical Nerve Stimulation (TENS), Microwave Diathermy (MWD), and William Flexion Exercises in patients with LBP due to spondylolisthesis receiving treatment at Anwar Medika General Hospital, Krian. This study used a case study design with six physiotherapy sessions involving TENS, MWD, and William Flexion Exercises. Parameters assessed included VAS, MMT, ROM, and ODI. The results showed that pain decreased from VAS 6 to 2; MMT scores improved; ROM increased up to 30°; and ODI scores improved from 40% to 16%. The combination therapy was effective and is recommended as a non-pharmacological management option for low back pain caused by spondylolisthesis.